PENERAPAN METODE BERMAIN PERAN DALAM MENGEMBANGKAN KARAKTER DAN KECERDASAN LINGUISTIK PADA SISWA SMP KELAS VIII DI PASRAMAN PURNA LINGGA PONDOK GEDE - Erma Wahyu Utami (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2019)
This study discusses the learning method using the role playing method in Pasraman with the aim of developing Linguistic character and intelligence. This research was conducted in Pasraman Purna Lingga Pondok Gede. The background of this research is to develop learning methods to vary, because previously in Pasraman Purna Lingga using conventional methods or lecture methods. The lecture method is considered less attractive because students are only silent, listening and easily bored for the writer trying to apply the role playing method, where students participate actively in the learning process. This study uses a qualitative descriptive approach in which the data collection uses interview techniques, observation and documentation in the Purna Lingga Pondok Gede area. From the results of the study using the role playing method that is applied to students of Class VIII Middle School characters in students has developed well, by using simulations through drama scripts students can know and understand the characters that are in the Ramayana story and applied in everyday life. Whereas for linguistic intelligence class VIII students are already good at using language and fluent in talking about knowing the accuracy of intonation, pronunciation, facial expressions and fluent in delivering the drama script. Keywords: Methods of Role Playing, Character, Linguistics